PENGARUH BEBAN KERJA, STRES KERJA TERHADAP TURNOVER INTENTION KARYAWAN DENGAN WORKPLACE WELLBEING SEBAGAI VARIABEL MEDIASI - Tiar Abdan Hisbih; Lili Karmela Fitriani; Odang Supriatna (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
This research aims to understand the impact of workload, work stress on turnover intention mediated by workplace well-being. The research population is the staff of the Permata Kuningan Hospital. The sampling technique used the Slovin technique resulted in 143 respondents. The research method used was quantitative descriptive, using a questionnaire tool distributed through googleform to 143 respondents. Structural Equation Model (SEM) based on Partial Least Square (PLS). Overview of the results of the study, the workload in the Permata Kuningan Hospital belongs to moderate, work stress is included in the low category, workplace well-being Permata Kuningan Hospital is in the high category as well as the turnover intention figure is belonged to low. As a result of the test of the hypothesis in this study, workload has a positive effect on work stress significantly. The higher the workload of the employee, the higher the level of work stress. Workload has no impact on workplace well-being. The workload has a positive impact on turnover intentions significantly. Work stress has a negative impact on workplace well-being. Work stress has a positive impact on turnover intentions. For the workplace well-being mediation role in mediating workload and work stress on turnover intention has no significant influence